Association between the systemic immune-inflammation index and the outcome of liver fibrosis in patients with chronic hepatitis C - Ma, Yuanji; Wang, Jiayi; Du, Lingyao; Tang, Hong (Frontiers in Medicine, 2024)
Background: The risk factors that influence the outcome of patients with chronic hepatitis C (CHC) are not fully understood. The systemic immune-inflammatory index (SII) is an independent prognostic factor for multiple diseases. However, the impact of the SII on the outcome of liver fibrosis is unclear. Methods: This prospective real-world study enrolled patients with CHC treated with sofosbuvir/velpatasvir. Logistic regression models were used to investigate the relationship between the SII and the outcome of liver fibrosis in treatment-naive patients. Liver fibrosis was assessed using aspartate aminotransferase to platelet ratio index (APRI) and fibrosis-4 index (FIB-4). Results: Of the 288 participants, the SII was 238.2 (153.0-358.2). The non-improved outcomes of liver fibrosis assessed with APRI (non-improved APRI) and FIB-4 (non-improved FIB-4) were 83.0% and 87.5%, respectively. Adjusted models showed that the SII was positively associated with non-improved APRI (adjusted OR (95% CI): 1.013 (1.009-1.017), P <0.001) and FIB-4 (adjusted OR (95% CI): 1.004 (1.001-1.007), P =0.012). Similarly, a higher SII was associated with a higher risk of non-improved APRI (adjusted OR (95% CI): 13.53(5.60-32.68), P <0.001) and FIB-4 (adjusted OR (95% CI): 5.69(2.17-14.90), P <0.001). The association with non-improved APRI was much more remarkable in patients with alanine aminotransferase <2 ULN, and the association with non-improved FIB-4 was remarkable in patients aged <50 years. Multiple imputation analyses confirmed the robustness of these results. Conclusions: Our findings suggested that the SII was positively associated with non-improved outcomes of liver fibrosis in patients with CHC. These results need to be validated in large-scale prospective cohorts.